COMPARISON OF LIPID PROFILE AND APOPROTEIN IN SEDENTARY WORKERS AND THOSE INVOLVED IN REGULAR EXERCISE - Gandapur, Abdus Salam Khan; Manan, Modoodul; Manan, Modoodul; Nazir, Ghazala; Uzma, Naeen; Chawla, Javaid Akhtar; Jadoon, Azhar; Tauqeer, Asya (Journal of Ayub Medical College Abbottabad, 2006)
Background: One of the important effects of exercise on human body is on the metabolic system especially on lipids; elevated lipids and lipoprotein are risk factors for coronary heart disease. This case-control study was conducted t o compare the lipid profile and apo-protein B levels in sedentary workers and subjects involved in regular exercise. Methodology: The study was conducted at Women Medical College Abbottabad, from July 2004 to January 2005. Subjects were civilians and army men involved in regular exercise for more than 6 months duration (test group) and sedentary workers (control group). The age, body weight, height, waist hip ratio and other related findings were recorded on a special proforma. Fasting blood samples were taken and were analyzed for lipid profile and apoprotein B levels. Statistical analysis was done by the Chi square and the S tudent t tests and level of significance was recorded. Result: The subjects comprised 29 army men, 24 civilians and 39 sedentary workers. Significant differences were found between the control and test groups for WHR, total cholesterol, HDL, LDL, Triglycerides, Apo B, and Cholesterol/HDL ratio; in addition the civilian group also showed significant differences from the control group in BMI values. Although LDL levels were lower in army than sedentary group, the difference was statistically nonsignificant. Significant differences were found between the army and civilian groups in age, HDL, Triglycerides and Apo B values. Conclusion: Long term aerobic exercise has beneficial effects in decreasing Apo- protein B levels, LDL levels and total cholesterol /HDL ratio. Exercise habits should be encouraged in general population to decrease the cardiovascular disease risk. Key Words: Exercise, lipid profile, apo-lipoprotein B.